Política fiscal e dívida pública: Uma abordagem teórica a partir de keynes e abba lerner - Garcia, Renato Vaz [UNESP] (My University, 2010)
The fiscal policies of national governments are an important instrument of economic policy, as they contribute directly or indirectly to growth and economic development. Since Keynes, the utilization of active fiscal policy is unavoidable during periods of crisis, especially a policy of public investment spending aimed at reducing macroeconomic uncertainty. In the same way, Abba Lerner and functional finances indicate the use of fiscal policy in favor of macroeconomic stability, and not according to a single objective of seeking equilibrium in the public accounts. However, at the present time, the debate on fiscal policy is not sufficient to guarantee public sector financial equilibrium. The article picks up on the contributions of Keynes and Abba Lerner regarding the importance of the public budget in economic activity, and discusses the present scenario for fiscal policy.
Fiscal policy and public debt: From a theoretical approach of keynes and abba lerner
Keywords: Abba lerner; Fiscal policy; Keynes; Public accounts; Public debt